APPLICATION OF RESTORATIVE JUSTICE IN HANDLING CHILD CRIMINAL CASES IN WONOSOBO DISTRICT COURT - Sentosa Lase, Haga (Jurnal Hukum Khaira Ummah, 2023)
The objective of this particular thesis are to find out whether the application of Restorative Justice in child crime management has been applied in Wonosobo District Court, to find out the obstacles which challenge the application of Restorative Justice and to find out how to overcome those obstacles in child crime management. This particular rersearch uses empirical law method which sess the law from the factual perspective and which observes how the law functions in the society using Juridical Sociological approach. The source of data that will be used is prioritized on primary data which are the data obtained from the respondents and the interview result from the Judges of Juvenile Justice who work in Wonosobo District Court and the secondary data such as library study and analyses from several recent critical writings and articles regarding law as well as other law related to the settlement of child crime management. The findings of the result show that in fact, Restorative Justice has been applied well in Wonosobo District Court in the child crime management by through a diversion process between the victim and the suspect by the Hakim Anak. The obstacle factor of Restorative Justice is actually caused by different perception regarding the meaning of justice among the people involved in diversion either the victims, victims’ families, the suspects, the suspects’ families, the law enforcement apparatus, and the society against the diversion implementation.Keywords: Restorative Justice, diversion, child crime.